2017
DOI: 10.1007/s12671-017-0850-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion and Psychological Distress in Adolescents—a Meta-analysis

Abstract: Research indicates that self-compassion is relevant to adolescents’ psychological well-being, and may inform the development of mental health and well-being interventions for youth. This meta-analysis synthesises the existing literature to estimate the magnitude of effect for the association between self-compassion and psychological distress in adolescents. Our search identified 19 relevant studies of adolescents (10–19 years; N = 7049) for inclusion. A large effect size was found for an inverse relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
210
6
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(255 citation statements)
references
References 87 publications
(178 reference statements)
27
210
6
12
Order By: Relevance
“…On the one hand, we found that selfcompassion-related therapies, compared to a control condition, successfully increase self-compassion and reduce levels of depression and anxiety with medium effect sizes. These results indicate that self-compassion is a psychological characteristic that can be modified in therapy, and this is of clinical interest given the relationship between self-compassion and psychopathology (MacBeth and Gumley 2012;Marsh et al 2018). However, this meta-analysis also found that self-compassionrelated therapies did not produce better outcomes than active control conditions.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…On the one hand, we found that selfcompassion-related therapies, compared to a control condition, successfully increase self-compassion and reduce levels of depression and anxiety with medium effect sizes. These results indicate that self-compassion is a psychological characteristic that can be modified in therapy, and this is of clinical interest given the relationship between self-compassion and psychopathology (MacBeth and Gumley 2012;Marsh et al 2018). However, this meta-analysis also found that self-compassionrelated therapies did not produce better outcomes than active control conditions.…”
Section: Discussionmentioning
confidence: 81%
“…Where possible, we also extracted depression and anxiety scores. We focussed on symptoms of depression and anxiety as key outcome variables since these have been identified as linked to self-compassion in previous meta-analyses (MacBeth and Gumley 2012;Marsh et al 2018). They are also common outcomes in RCTs, so it was likely that we would identify a sufficient number of studies to calculate summary estimates of the effect of therapy on these two variables.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…A potential mechanism of the effect achieved with these modules could be the reduction in loneliness as has been found for mindfulness‐based stress reduction training (Creswell et al ., ). Similarly, compassion‐focused interventions may help to ameliorate negative feelings (Marsh, Chan, & MacBeth, ) associated with loneliness. For example, self‐compassion enables individuals to appraise their experiences as part of a ‘common/shared humanity’, providing some relief or even feelings of connectedness with others.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the aesthetic dimension, while serving as a basis for judgment and competition, could also provide leverage for processing issues related to the development of self-compassion and self-acceptance (see, Neff and McGehee, 2010). When engaging in DFO, self-compassion and acceptance could be accompanied by a loving, flexible gaze directed toward both the aesthetics of the final product, as well as toward the creative self and the creative process (see also, Marsh et al, 2017). Moreover, focusing on the aesthetics of the visual object might allow for the adoption of a flexible perception toward the concept of beauty, which could become a way to process and contain the extensive preoccupation that adolescents have with their physical selves (Hargreaves and Tiggemann, 2004;Burnette et al, 2017).…”
Section: Reflection Between Similarities and Differencesmentioning
confidence: 99%